Analisis Faktor-Faktor Yang Mempengaruhi Dividend Payout Ratio Pada Saham Consumer Good Industry Yang Tercatat Di Bursa Efek Indonesia - Beta Asteria; Dyah Ayu Widiastuti (Jurnal Solusi, 2019)
Determination of dividend policy related to profit sharing decisions obtained by the company. Management will make a decision whether management will share profits with shareholders as dividends or retain profits for investment funding to be made in the future. Dividend policy is important to study because it has an impact on company value reflected in stock prices. This study aims to analyze the effect of Return on Assets (ROA), Debt to Equity (DER) and Current Ratio (CR) to Dividend Payout Ratio in Consumer Good Industry stocks listed on the Indonesia Stock Exchange in 2014-2017. The sampling technique in this study is Purposive Sampling. Of the 49 Consumer Good Industry shares, only 8 were included in the criteria for the study sample from 2014-2017, so the number of research samples was 36. The regression analysis method was used in this study, namely 1. T test to examine the effect of independent variables on the dependent variable Partial; and 2. F test to examine the effect of independent variables on the dependent variable simultaneously. The results of the study prove that Return on Assets (ROA) has a significant effect on Dividend Payout Ratio in Consumer Good Industry shares listed on the Indonesia Stock Exchange in 2014-2017. Whereas Debt to Equity (DER) and Current Ratio (CR) were not proven to influence partially to the Dividend Payout Ratio in Consumer Good Industry shares listed on the Indonesia Stock Exchange in 2014-2017. As well as the results of the study prove that Return on Assets (ROA), Debt to Equity (DER) and Current Ratio (CR) simultaneously have a significant effect on Dividend Payout Ratio (DER) in Consumer Good Industry shares listed on the Indonesia Stock Exchange in 2014- 2017.